Suction Variation of a Single Mature Tree on Top of Tropical Residual Soil - S Daud,; Zolkepli, Muhammad Farhan; Ishak, Mohd Fakhrurrazi; Abu Talib, Zaihasra (International Journal of Integrated Engineering, 2024)
This paper discusses the investigation of an active root tree zone located on top of a slope. This section of slope generated matric suction due to tree water uptake. A field monitoring program was conducted to collect matric suction data at the slope with two conditions: in the absence of a tree and with a tree located on top of a tropical residual soil slope [1]. The variation in matric suction values and matric suction profiles response to the tree water uptake and rainfall are investigated. Matric suction significantly increased in the vicinity of the tree on top of the slope compared to the slope without a tree. The variations of matric suction response due to climate change occur significantly at the swallow of the slope and decrease gradually with depth. The decreases of matric suction occur after a long duration of intense rainfall. This was an initial condition before the water uptake driven by the active root tree generated maximum matric suction (low moisture content). Analyses from matric suction profiles revealed that the majority of matric suction changes were greater near tree trunks (< 4.4 m) and at shallow depths (0.25m) [2]. The contours of matric suction profiles are presented to reveal moisture flow due to tree water uptake. This investigation provides that the viewed contribution of a single mature tree significantly alters the matric suction or moisture variation distribution driven by transpiration in an unsaturated soil slope. It considers that preserving mature trees can improve soil properties in modern slope designs.